The Influence of Breakfast Habits on the Concentration of Study Among Medical Students of YARSI University Class of 2021 and Its Review from an Islamic Perspective - Mufidah Trinanda; Pusparini, Miranti; Fazlurrahman Anshar, Muhammad; Romadhiyani, Qomariyah (Fakultas Kedokteran Universitas YARSI, 2025)
Breakfast is an important thing to do in the morning because it is useful for providing the energy needed by the body. Food consumed in the morning can maintain stable blood sugar which has an impact on increasing a person's focus and concentration. Concentration in learning can help students to master the material given, increase enthusiasm and motivation to be more active during the learning process. This study aims to determine the effect of breakfast habits on the learning concentration of YARSI University Medical Students, Class of 2021 and to examine its review from an Islamic perspective. This study used a cross-sectional design with a sample of 175 respondents selected by purposive sampling. Data were collected through an online questionnaire that included information about breakfast habits and factors that influence students' learning concentration levels. The results showed that most respondents (62.3%) only had breakfast for 1-3 days in 1 week. A total of 157 respondents (89.7%) were in the good concentration category and 18 respondents (10.3%) were in the poor concentration category. Bivariate analysis using the Chi-Square test obtained a p-value of 0.014 (<0.05) so it can be concluded that there is an influence of breakfast habits on learning concentration in students of the Faculty of Medicine, YARSI University, class of 2021.